Ketepatan Pemorsian Sayur Terhadap Standar Porsi Makanan Biasa - Sabrina Apriliyani; Luh Suranadi; Susilo Wirawan; AASP Chandradewi (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background. Consumption of vegetables and fruit body needs for vitamins, minerals and fiber in achieving a healthy diet as recommended by guidelines of balanced nutrition for optimal health. Most vitamins and minerals found in fruits and vegetables has a function as an antioxidant that may reduce the incidence of non-communicable diseases related to nutrition, as a result of the excess or deficiency. Large portions often becomes very important when serving food, especially in the food pemortion advantages and disadvantages still occur because no portion of the right size in pemortion food. Pemortion these foods should be according to the standard portion that has been set by the installation of a hospital nutrition. Huge portions, will directly influence the nutrients contained in a food. Purpose Knowing picture vegetable pemortion accuracy of the standards usual food servings at lunch in Tabanan Hospital. Research Methods. This research is an observational study. The study was conducted on 22 to 30 March 2019 in BRSUD Tabanan. The data were taken using accidental sampling method. Samples taken care third grade. Research Result. Large servings of vegetables at lunch for ordinary food in hospitals Tabanan as follows: vegetable tamarind 160.7 grams, vegetable nodes 175 grams, vegetable ointment 170.4 grams, vegetable bobor 131.8 grams, vegetables, tamarind 177 grams, vegetable soup 104.5 grams, vegetable lodeh 102.6 grams and 71.4 grams of vegetable ointment. Power pemortion obtained are four power pemortion with vocational education and universities. Conclusion. Great accuracy servings of vegetables served by 4 workers pemortion average is not appropriate because more than a standard portion